In vivo study and thermodynamic investigation of two lanthanum complexes, La(dpp)3 and La(XT), for the treatment of bone resorption disorders. Issue 11 (12th August 2015) - Cawthray, J. F.; Weekes, D. M.; Sivak, O.; Creagh, A. L.; Ibrahim, F.; Iafrate, M.; Haynes, C. A.; Wasan, K. M.; Orvig, C.
Abstract : Lanthanum could act as a preventative measure against bone resorption disorders; two compounds are thoroughly investigated both in vivo and ex vivo as potential oral drug candidates. Abstract : Bone density diseases such as osteoporosis affect a significant number of people worldwide. Lanthanide ions are functional mimics of calcium ions, able to substitute for Ca 2+ in the bone mineral component, hydroxyapatite (HAP). Bone undergoes a continuous remodelling cycle and lanthanides can affect this cycle, exerting a positive influence on bone mineral. We have been engaged in efforts to find new lanthanide containing complexes as active agents for treatment of these diseases and have identified two lead compounds, 3-hydroxy-1, 2-dimethylpyridin-4(1 H )-one (Hdpp) and a phosphinate-EDTA derivative, bis[[bis(carboxymethyl)amino]-methyl]phosphinate (H5 XT). In this paper, we report in vivo data for the first time for the two lead compounds. The pharmacokinetics of La(dpp)3 suggest the complex is rapidly cleared from plasma. We demonstrate that La 3+ accumulates in the bone following IV dose of either La(dpp)3 or La(XT) and we have investigated the influence of each chelating ligand on the incorporation of La 3+ into HAP using ITC and HAP-binding studies.